2018
DOI: 10.1088/1752-7163/aa9856
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in cardiac surgery: towards consensus on biomonitoring, diagnostic tools and therapeutic implementation

Abstract: This review focuses on oxidative stress and more specifically lipid peroxidation in cardiac surgery, one of the fundamental theories of perioperative complications. We present the molecular pathways leading to lipid peroxidation and integrate analytical methods that allow detection of lipid peroxidation markers in the fluid phase with those focusing on volatile compounds in exhaled breath. In order to explore the accumulated data in the literature, we present a systematic review of quantitative analysis of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…In addition, both SOD and GPx are antioxidant enzymes that catalyze the reduction of glutathione. 30 , 31 The conversion of MDA and the activities of SOD and GPx in the cortex of mice with TBI indicate that oxidative stress occurs following TBI. Apart from that, the results of this study also showed that the treatment with ketamine partly relieves this impact, suggesting that ketamine could attenuate TBI-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both SOD and GPx are antioxidant enzymes that catalyze the reduction of glutathione. 30 , 31 The conversion of MDA and the activities of SOD and GPx in the cortex of mice with TBI indicate that oxidative stress occurs following TBI. Apart from that, the results of this study also showed that the treatment with ketamine partly relieves this impact, suggesting that ketamine could attenuate TBI-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative approach has irrefutably demonstrated the significant contribution of diathermy to overall oxidative stress and identified increased ethylene associated with regional myocardial ischemia on an individual basis. It can be concluded that sensitive, totally noninvasive, and real-time analysis of lipid peroxidation using breath ethylene is feasible in the clinical and perioperative setting [68]. Mid-infrared OPOs are considered amongst the most useful tools for sensitive LPAS gas sensing, due to their high power (Watt level), wide tuning range, and ease of tunability.…”
Section: Principles and Overview Of Photoacoustic Spectroscopymentioning
confidence: 99%
“…Lipid peroxidation, caused by increased ROS and RNS, is linked to many acute and chronic diseases of adulthood such as MOF, hemorrhagic and septic shock, ARDS, acute lung injury, cardiovascular pathology requiring surgery, aging, atherosclerosis, Parkinson, Alzheimer, diabetes mellitus, cataracts and rheumatoid arthritis, and several diseases of the neonatal period (Takeda et al, 1984; Hammond and Hess, 1985; Bertrand et al, 1989; Richard et al, 1990; Quinlan et al, 1996; Carpenter et al, 1998; Lamb et al, 1999; Motoyama et al, 2003; Comporti et al, 2004; Quinlan et al, 2004; Fläring et al, 2005; Laplace et al, 2005; Niki et al, 2005; Saugstad, 2005; Huet et al, 2007; Signorini et al, 2008; Giustarini et al, 2009; Briones and Touyz, 2010; Giacco and Brownlee, 2010; Khaper et al, 2010; Romano et al, 2010; Barrera et al, 2018; Maiorino et al, 2018; Mátyás and Zaharie, 2018; Moore et al, 2018; Orban and Singer, 2018; Perrone et al, 2018; Romano et al, 2018).…”
Section: Redox Biology and Oxidative Stressmentioning
confidence: 99%